EFFECT OF BOTANICAL INSECTICIDES NEEMAZAL-T/S AND PYRETHRUM APPLIED ALONE AND IN COMBINATION WITH DIFFERENT ORGANIC PRODUCTS ON THRIPS TABACI POPULATION DENSITY (Acta Entomologica Serbica, 2014)
The trial was conducted with spring forage pea (Pisum sativum L.) from 2011-2013 in the experimental field of the Institute of Forage Crops, Bulgaria. The effect of three insecticides was studied:  NeemAzal T/S®, Pyrethrum FS EC (botanical insecticides) and Nurelle D (synthetic insecticide) applied alone and in combination with the growth regulators Polyversum (biological growth regulator and fungicide) and Flordimex 420 (synthetic growth regulator); and an organic foliar fertilizer known as Biofa on Thrips tabaci population density. The treatment was conducted once (at budding stage) and twice (at budding and flowering stages). Between the studied biological insecticides against Thrips tabaci (Thysanoptera: Thripidae) Pyretrum FS EC was distinguished by its higher protective effect and fast initial activity, while NeemAzal-T/S exhibited slow initial activity and a relatively weak increasing after-effect. Combined use of the bioinsecticides with the organic foliar fertilizer Biofa and growth regulator Polyversum established synergism. The synergistic effect was more pronounced in combinations with Biofa. The highest efficacy among the organic products was found under combined use of Pyrethrum FS EC and Biofa whose protective effect approximated that of Nurele D Chlorsyrine 550 EC. The double treatment of plants (at budding and flowering stages) with Pyrethrum and NeemAzal reduced the density of thrips by 28.9% and 20.1% respectively compared to the single application, without consideration of the method of use. The most efficient combination among organic products was the use of Pyrethrum with Biofa where the density of thrips decreased by 53.7%, followed by Pyrethrum with Polyversum (by 44.0%) and NeemAzal with Biofa (by 39.5%) irrespective of the stage of treatment.